Urinary tract infection among undergraduate female students at school of heal th sciences Universiti Sains Malaysia: prevalence and awareness - Puso, Caroline Emma (Universiti Sains Malaysia, 2016)
Urinaiy tract infection (UTI) is the most common bacterial infection in women. Substantial evidence can be found in the literature to show the prevalence and awareness as well as facts on UTI including risk factors, etiology, sign and symptoms and complications. The objective of this study was to detennine the prevalence and awareness of UTI among undergraduate students at School of Health Sciences, Universiti Sains Malaysia. ll1is crosssectional study was done on 137 fe1nale students by random sampling. Validated questionnaires were distributed to the undergraduate female students that fit the inclusion criteria. Data was analyzed using descriptive statistics and Pearson Chi-Square. Resuhs showed the prevalence of UTI among students was low which was at 6.57%. As for awareness, most the students (n=77, 56.2%) were highly aware of UTI. Association was found between treatrnent seeking behavior and awareness of UTI (p>0.05). Further study need to be done involving larger sample size with support from family and health professionals.